Assessment of clonality and serotypes of Streptococcus mutans among children by multilocus sequence typing. (7th October 2015) - Momeni, Stephanie S.; Whiddon, Jennifer; Cheon, Kyounga; Moser, Stephen A.; Childers, Noel K.
Abstract : Studies using multilocus sequence typing (MLST) have demonstrated that Streptococcus mutans isolates are genetically diverse. Our laboratory previously demonstrated clonality of S. mutans using MLST but could not discount the possibility of sampling bias. In this study, the clonality of randomly selected S. mutans plaque isolates from African‐American children was examined using MLST. Serotype and the presence of collagen‐binding proteins (CBPs) encoded by cnm/cbm were also assessed. One‐hundred S. mutans isolates were randomly selected for MLST analysis. Sequence analysis was performed and phylogenetic trees were generated usingstart 2 andmega . Thirty‐four sequence types were identified, of which 27 were unique to this population. Seventy‐five per cent of the isolates clustered into 16 clonal groups. The serotypes observed were c ( n = 84), e ( n = 3), and k ( n = 11). The prevalence of S. mutans isolates of serotype k was notably high, at 17.5%. All isolates were cnm/cbm negative. The clonality of S. mutans demonstrated in this study illustrates the importance of localized population studies and are consistent with transmission. The prevalence of serotype k, a recently proposed systemic pathogen, observed in this study, is higher than reported in most populations and is the first report of S. mutans serotype k in a United States population.